PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WSIATA PERMANDIAN AIR PANAS MANTIKOLE - Priantini, Kadek Dwi; Triawati, Komang; Putra, I Gede Adiyana (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2025)
This study aims to analyze the forms of community participation in the management of the Mantikole Hot Springs tourist attraction and identify the factors that influence it, with the background of the need for local community involvement to ensure the sustainability and benefits of tourism management for the surrounding community. The research method used is descriptive qualitative through data collection techniques in the form of interviews, observations, and documentation, with inductive data analysis based on the theory of community participation which includes levels, forms, and factors that influence participation. The results of the study indicate that community participation in the tourist attraction includes planning, implementation, and evaluation of management, while the factors that influence it consist of internal factors (individual characteristics) and external factors (government policies, leadership, and communication). The conclusion of this study emphasizes the need to increase community capacity and synergy between the community, government, and other stakeholders to encourage more effective participation in tourism management.